THE INFLUENCE OF INVESTMENTS, GOVERNMENT EXPENDITURE AND LABORS ON ECONOMIC GROWTH IN ACEH PROVINCE - Romi Juliansyah; Nazamuddin Nazamuddin; Faisal Faisal (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2018)
AbstractThis study aims to determine theInfluence of investment, governmentspending and labors on economic growth inAceh province. The method used usingmultiple regression analysis (Ordinary LeastSquare). The data in this study is secondarydata in the form of Aceh economic datafrom 1991 - 2017 sourced from the CentralBureau of Statistics (BPS), the Agency forInvestment and Promotion of Aceh, and theDinas Keuangan Aceh. The results showedthat investment variables, governmentexpenditures and manpower have a positiveand significant impact on economic growthin Aceh province with the value ofcoefficient of determination (R2) of 0.92which means the equation of economicgrowth sector / GDP is able to be explainedby independent variables of investment,government and labor with a confidencelevel of 92%. The conclusion of this study isthat economic growth can be increasedthrough increased investment, higher laborproductivity and government expenditure tobe oriented on community economicdevelopment.